CMOS Class C amplifier for motion detection. (2021) - Kaleel Rahuman, A.; Kavitha, A.; Saleem Raja, A.; Narmadha, C.; Mohanraj, P.
Abstract: Noncontact detection of human vital signs based on miniaturized Doppler radar systems (DRSs) can be widely used in healthcare and biomedical applications. Although significant progresses have been achieved, a reliable wireless vital signs detection in the presence of large-scale random human body movements remains a technical challenge. This work proposes a cost-effective UWB Doppler radar system for movement detection from a mobile radar platform. The proposed radar architecture concurrently transmits the fundamental signal component (FSC) and it use a Complex Wavelet Transform algorithm for change detection using an Ultra-Wideband (UWB) impulse. CWT based approach is better than the existing method and it takes less response time which is more suitable for detection with high accuracy. Signal Peak Analysis & Time Interval Estimation performed to find out normalized magnitude change detection of signal. UWB radar works well in poor visibility conditions. Spectral constraints placed on radar systems by regulatory agencies require the design of highly linear amplifiers. Class C amplifier contributes important spectral part in radar system. In this work also design cascaded multiple threshold CMOS class C amplifier for motion detection. Experimental results show that the proposed radar system is capable of extracting human movement, even in the presence of a large radar platform movement with high SNR and accuracy rates.